中国利用外资分析及其政府外债管理探讨 = Use of foreign capital and management of government's external debt in China - 宁金彪 Ning, Jinbiao (2010)
本文的主要目的是探讨在外债管理方面的重大问题在中国的外国资本和管理问题也由中国政府遇到。文中，我们利用国家会计身份使用，这两个差距分析以及两个时期的消费和储蓄模型来解释对外资的需求。尽管中国已经经历了高储蓄率，经常帐盈余和高外汇储备。但是，中国仍然是吸引大量外国资本。这两个标准的差距分析和其他经济理论似乎无法解释这种现象。该文件属性，这种现象的事实，中国需求（1）外国转让技术的外国资本;（二）转让的管理理念和企业文化;（3）开发潜力巨大的国内市场;（4）开拓国际市场网络跨国公司;及（5）创造就业机会。 The major aim of this paper is to discuss major issues of foreign capital in China and also management problems encountering by the Chinese Government in managing its external debt. In the paper, we make use of national accounting identities, the two gap analysis as well as two period model of consumption and savings to explain the needs for foreign capital. Even though China has been experiencing high saving rate, current account surplus and high external reserves. However, China is still attracting huge amount of foreign capital. The two gap analysis and other standard economic theories seem to have failed to explain such phenomenon. The paper attributes such phenomenon to the fact that China needs foreign capital for (1) transfer of foreign technology; (2) transfer of management philosophy and corporate culture; (3) exploiting potentials of huge domestic market; (4) exploiting international market network of Multinational corporations; and (5) job creation.